In Silico Study of the Antibacterial Activity of Bioactive Compounds from Portulaca oleracea L. Herb Extract against Propionibacterium Acnes - Nadhifa Dini Maulida; Nur Aqidah; Nanda Ma’rifatul Ilmiah; Maprilia Nur Nabillah; Niken Ayu Ramadhany; Mohammad Rofik Usman (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Acne vulgaris is a common dermatological condition primarily caused by the bacterium Propionibacterium acnes. The use of natural compounds as alternative therapies has gained attention due to their lower side effects compared to synthetic agents. This study aimed to evaluate the antibacterial potential of bioactive compounds present in purslane (Portulaca oleracea L.) herbs against P. acnes through an in silico approach. Out of 15 identified compounds, 12 satisfied Lipinski’s parameters, and 9 compounds were selected for further analysis. Pharmacokinetic and toxicity predictions were performed using the pkCSM platform to determine the ADMET profiles, while ligand–receptor interactions were analyzed via molecular docking against the Exo-x-sialidase protein target (PDB ID: 7LBV). The ADMET prediction results indicated that most compounds exhibited good solubility, high absorption, moderate skin permeability, and favorable distribution and metabolism profiles. Docking visualization revealed the presence of hydrogen bonds and hydrophobic interactions with key residues at the receptor’s active site. Interestingly, butylated hydroxytoluene demonstrated the lowest binding energy (–6.56 kcal/mol), which was better than that of the positive control (–6.17 kcal/mol), indicating a stronger binding affinity. Overall, Portulaca oleracea shows promise as a natural source of antibacterial compounds against P. acnes, warranting further in vivo investigation.